Smart Economy Kreatifitas Kelurahan Siantan Hilir Melalui Peningkatan Potensi Kawasan Kampung Sayur Kuat Sihir - Andi Zulestari; Palupi Ikayanti; Julius Judhi; Deni Maulana; Taufik Wibowo; Nunik Hasriyanti; Achmad Eko Yanuar; Muhammad Hidayat (Politeknik Negeri Pontianak, 2026)
Kampung Gambut Siantan Hilir (Kuat Sihir) is an agro-tourism area in North Pontianak District. This area is the main supporter of vegetable needs for the people of Pontianak City and its surroundings. Kuat Sihir was previously empty land in the form of peat land that could not be utilized. Residents living in the surrounding area then tried to grow mustard greens and spinach to meet their daily needs, then they grew and could be sold until they reached themain market in PontianakCity. They use almost all the empty peat land in Siantan Hilir Village to produce various types ofplants and vegetables. However, the vegetable products produced need to be diversified into derivative products so that they can increase the economic value of the vegetable products. The derivative products that have been made are noodles from mustard greens and spinach, pineapple syrup and sweet potato rengginang. Apart from derivative products to support agrotourism, the existence of connecting routes in the vegetable village area also needs to be improved, especially bridges as circulation routes in the area for visitors and vegetable farmers. Systematic and developed planning is needed to increase the economic value of the area as an agro-educotourism area in North Pontianak. Pontianak State Polytechnic, Department of Architectural Engineering strives to be involved in community service to apply the knowledge, skills and competencies possessed by students in developing the Kuat Ajaib area so that it can become a tourist area that has attractions, access, supporting facilities, accommodation, activities and stakeholder support.